KREATIVITAS PEMBINA DALAM PERAYAAN ANAK MINGGU GEMBIRA - Kurniadi, Benediktus Benteng (IN VERITATE LUX, 2019)
The purpose of this research is to determine the creativity of supervisors in the Happy Sunday celebration. The research method used in the research is a qualitative approach. Based on qualitative research, informants were determined using purposive sampling and snowball sampling techniques. The location of this research is Stasi St. Albertus, Saribu Dolok Parish. The findings of this research show that the creativity used by companions is quite varied, namely telling stories and singing. play, and song and movement. Happy Sunday children really enjoy this creativity so they are happy to take part in Happy Sunday celebrations. Keywords: creativity; mentor; happy Sunday children